INVESTIGATION OF MECHANICAL BEHAVIOR OF POLYMERIC FOAM MATERIALS REINFORCED BY OIL PALM EMPTY FRUIT BUNCHES (OPEFB) FIBERS DUE TO STATIC AND DYNAMIC LOADS - Zulfikar, Achmad Jusuf; Umroh, Bobby; Siahaan, Muhammad Yusuf Rahmansyah (JMEMME (JOURNAL OF MECHANICAL ENGINEERING, MANUFACTURES, MATERIALS AND ENERGY), 2019)
Polymeric composite foam with EFB fiber reinforced is new material that can be utilized as an alternative engineering material. EFB fiber utilization becomes the center of subject in this research. Moreover, these composites are unique with the presence of cavities (foam) in the matrix of unsaturated polyester resin. It results a decrease in density of the material that formed, and obtain a thermoset polymer composite material lighter than any else similar type. The objective of this study is to obtain the best manufacturing techniques of composite material, the mechanical behavior of these materials due to tensile static loading and high strain rate impact, and the distribution of foam that occur in the material that formed as a result of blowing agent (BA) from the type of polyurethane (PU). In this research, the sample formed into standard specimen of testing, such as ASTM D638 for static tensile test, and impact test specimen. Mechanical’s behaviors that are obtained in this research are density, tensile strength, modulus of elasticity (E), the incident stress, and dynamic modulus of elasticity of the material. For static testing was performed according to standard ASTM D638 tensile and impact test using the Kolsky’s method. To know the distribution of foam that occur in the material, were observed using Scanning Electron Microscope instrument (SEM). To determine the stress distribution in this material, then conducted a computer simulation using Ansys. The best result obtained by the composition of this material based on material composition, which resin consumption can be reduced by the presence of BA as well as mechanical strength, good enough for molding. The best composition in this study will be used in subsequent studies, namely the design and manufacture of traffic cones from this material.